Divergent paths : the academy and the judiciary - Posner, Richard A. (Harvard University Press, 2016)
"Judges and legal scholars talk past one another, if they have any conversation at all. Academics couch their criticisms of judicial decisions in theoretical terms, which leads many judges - at the risk of intellectual stagnation - to dismiss most academic discourse as opaque and divorced from reality. Richard Posner turns his attention to this widening gap within the legal profession, reflecting on its causes and consequences and asking what can be done to close or at least narrow it. The shortcomings of academic legal analysis are real, but they cannot disguise the fact that the modern judiciary has several serious deficiencies that academic research and teaching could help to solve or alleviate. In U.S. federal courts, which is the focus of Posner's analysis of the judicial path, judges confront ever more difficult cases, many involving complex and arcane scientific and technological distinctions, yet continue to be wedded to legal traditions sometimes centuries old. Posner asks how legal education can be made less theory-driven and more compatible with the present and future demands of judging and lawyering. Law schools, he points out, have great potential to promote much-needed improvements in the judiciary, but doing so will require significant changes in curriculum, hiring policy, and methods of educating future judges. If law schools start to focus more on practical problems facing the American legal system rather than on debating its theoretical failures, the gulf separating the academy and the judiciary will narrow."--Book jacket / publisher's website.